Spherical sliding isolation bearings with adaptive behavior experimental verification. - Fenz, Daniel M. (Earthquake engineering & structural dynamics.)
This paper describes an experimental program to examine the force displacement behavior of a class of multi-spherical sliding bearings. The primary goal of the experiments is to test the validity of the theory developed in a companion paper that describes the behavior of these devices. Experimental work consisted of testing the three primary variations of these bearings in several configuratlions of different friction and displacement capacities. Most tests were carried out at slow speeds; however, some testing was also conducted at high speed (up to approximately 400 mm/s) to examine the behavior under dynamic conditions. The results of experimental testing were generally found to be in very good agreement with the analytical results. It is shown that the forces and displacements at which transitions in stiffness occur are predictable and therefore controllable in design. Furthermore, the underlying principles of operation were confirmed by the fact that starting and stopping of sliding on different surfaces occured as expected from theory.